Innovative use of sheep and goats by women in climate smart villages in Kenya - CGIAR Research Program on Livestock (2018)
The CGIAR led project thus introduced improved strains of resilient but more productive indigenous breeds of Gala goats and Red Maasai sheep for crossbreeding with the local breeds and has resulted in women taking a lead in community led breeding programmes resulting in crosses with better performance and desirable traits.